2016
DOI: 10.1093/jscr/rjw184
|View full text |Cite
|
Sign up to set email alerts
|

An unusual presentation of a rare disease: posterior reversible encephalopathy syndrome following abdominal sepsis

Abstract: Posterior reversible encephalopathy syndrome (PRES) is an unusual disease of unknown incidence and cause. There are a wide range of associated, predisposing medical causes to include pregnancy, renal failure, immunosuppressive medication administration and hypertension. The diagnosis is made following the radiographic identification of characteristic vasogenic edema in the setting of neurologic impairment. A significant portion of patients will have long-term, if not permanent, sequelae of the disease. We pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
(11 reference statements)
1
4
0
Order By: Relevance
“…The breakdown of autoregulation results in hyperperfusion and the subsequent extravasation of fluid into the interstitium of the brain tissue at the periphery of the arterial territories. [ 7 15 16 ] This theory was confirmed by Zeeman et al . who showed that patients with PET/eclampsia develop a significant increase in the cerebral blood flow, which causes vasogenic edema.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The breakdown of autoregulation results in hyperperfusion and the subsequent extravasation of fluid into the interstitium of the brain tissue at the periphery of the arterial territories. [ 7 15 16 ] This theory was confirmed by Zeeman et al . who showed that patients with PET/eclampsia develop a significant increase in the cerebral blood flow, which causes vasogenic edema.…”
Section: Discussionsupporting
confidence: 53%
“…and has since then been recognized in a growing number of pathological conditions such as preeclampsia toxemia (PET), eclampsia, hypertensive encephalopathy, autoimmune diseases, infection/sepsis, and the use of cytotoxic or immunosuppressive drugs. [ 1 4 5 6 7 ] Among these, PET or eclampsia has been cited in the literature as the most common cause of PRES. [ 3 ] PET is defined as a new onset of hypertension and proteinuria that appears after the 20 th week of gestation in a previously normotensive woman, and it occurs in 2%–3% of all pregnancies.…”
Section: Introductionmentioning
confidence: 99%
“…Other sequelae of intracranial hypertension may be present as well, contributing to the high variability in clinical presentation [4]. The PRES is often found with characteristic findings on neuroimaging studies including edema in the posterior cortical white matter.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it has been known by various names such as reversible posterior leukoencephalopathy syndrome, reversible posterior cerebral edema syndrome, and reversible occipital parietal encephalopathy [2,3]. PRES was first described in 1996 by Hinchey et al in patients with acute neurological symptoms and since then it has been recognized in different pathological conditions such as preeclampsia, eclampsia, hypertensive encephalopathy, autoimmune diseases, renal failure, infection, and the use of cytotoxic or immunosuppressive drugs [1,[3][4][5][6][7][8][9]. Among these, preeclampsia and eclampsia are the most common causes of PRES.…”
Section: Introductionmentioning
confidence: 99%